Government Regulation of Advertising in the Eurasian Economic Union: Contradictions of Public Policy and Advertising Ethics - Bykov, Il’ia A.; Cherkashchenko, Tatiana A.; Dorskii, Andrei Y.; Kaverina, Elena A. (International Journal of Economics and Financial Issues, 2015)
The article deals with the problems of government regulation of advertising industry in the member states of the Eurasian Economic Union (EAEU). The main purpose of the study includes evaluation of attitudes to the moral issues in advertising practice as well as government policy on the problem of unethical advertising. The study applies methodological framework of policy analysis toward the regulation of unethical advertising in the countries of the EAEU. The authors find out that there is no coherent public policy in this field in the EAEU. While Russia attempts to apply international standards with self-regulation mechanisms in order to deal with unethical advertisements, the other member states prefer to use strict governmental control. In Russia, there are two opposite tendencies: while mass media assign part of regulation to the government, the government does not want to adopt this role. The courts in Russia prefer reactive regulation of advertising, usually trying to evade even obvious law cases. At the same time, facing no resistance from either governments or societies, some part of advertising industry tends to abuse ethic norms. The authors claim that this situation undermines the process of integration and differs significantly advertising industry in the countries of EAEU from advertising, for example, in the member states of the European Union. Keywords: Eurasian Economic Union, advertising, government regulation, ethics, policy analysis JEL Classifications: M3; K2; F2; F6